Analisis Pengaruh Budaya Organisasi, Kepemimpinan Islami, Kompensasi dan Motivasi Terhadap Kinerja Karyawan PT. Migas Mandiri Pratama (MMP) Kalimantan Timur - Yuliani, Irma (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
The success of a company can’t be separated from the role of its employees or human resources who have expertise and professionalism in their fields. the purpose of this study was to determine how much influence organizational culture, islamic leadership, compensation and motivation on employee performance of PT Migas Mandiri Pratama (MMP) East Kalimantan partially and simultaneously and also to determine the variables that have the most influence on employee performance. The research method used is quantitative research. The population used was 32 respondents and the sampling technique was saturated sampling. The analysis technique used is multiple regression analysis with SPSS 25 data processing tools. The results of this study indicate that the organizational culture variable has a significant effect on employee performance and the motivation variable has a significant effect on employee performance. However, the islamic leadership variable has no significant effect on employee performance and the compensation variable has no significant effect on employee performance. The implication of this research is for the company to continue the good things that have been done in its efforts to maintain working relationships with employees to create a situation where employees become productive, committed, and loyal to the company.